2022
DOI: 10.3390/plants11050579
|View full text |Cite
|
Sign up to set email alerts
|

Papaya Leaf Curl Virus (PaLCuV) Infection on Papaya (Carica papaya L.) Plants Alters Anatomical and Physiological Properties and Reduces Bioactive Components

Abstract: Papaya leaves are used frequently for curing scores of ailments. The medicinal properties of papaya leaves are due to presence of certain bioactive/pharmacological compounds. However, the papaya leaf curl virus (PaLCuV), a geminivirus, is a major threat to papaya cultivation globally. During the present investigation, we observed that PaLCuV infection significantly altered the anatomy, physiology, and bioactive properties of papaya leaves. As compared to healthy leaves, the PaLCuV-infected leaves were found to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 64 publications
0
12
1
Order By: Relevance
“…The results of proline measurement revealed that healthy plants tended to have higher proline levels compared to diseased plants, except for GMP 7 (Figure 7). Results showed that ScSMV infection decreased proline levels and this was in disagreement with findings from previous experiments showing virus infection stimulated the increase of proline accumulation in leaves plants (Mohanty & Sridhar, 1982;Pazarlar et al, 2013;Bassiouny et al, 2015;Soni et al, 2022). However, the results of this study were in line with the findings of Hosseini et al (2021).…”
Section: Proline Contentcontrasting
confidence: 83%
See 1 more Smart Citation
“…The results of proline measurement revealed that healthy plants tended to have higher proline levels compared to diseased plants, except for GMP 7 (Figure 7). Results showed that ScSMV infection decreased proline levels and this was in disagreement with findings from previous experiments showing virus infection stimulated the increase of proline accumulation in leaves plants (Mohanty & Sridhar, 1982;Pazarlar et al, 2013;Bassiouny et al, 2015;Soni et al, 2022). However, the results of this study were in line with the findings of Hosseini et al (2021).…”
Section: Proline Contentcontrasting
confidence: 83%
“…Proline accumulation is a common metabolic response of plants to both abiotic and biotic stress. Previous experiments found that virus-infected plants increased proline content in plant tissues (Mohanty & Sridhar, 1982;Pazarlar et al, 2013;Bassiouny et al, 2015;Soni et al, 2022). Chen and Dickman (2005) described that when plants are infected by microbial pathogen, they produce reactive oxygen species (ROS) that induced programmed cell death in the plant cells at the infection site to effectively wall off the pathogen and terminate the disease process.…”
Section: Discussionmentioning
confidence: 99%
“…The most abundant species of plant pathogens include Agrobacterium spp., Erwinia spp., Pseudomonas spp., Ralstonia spp., and Xanthomonas spp., which are usually disseminated by various biotic and abiotic factors; and their entry into plants takes place through plants wounds/natural openings like lenticels, hydathodes, or stomata followed by their possession of the inter cellular spaces called apoplast of various tissues/xylem (Abramovitch et al, 2006). Despite plants possess innate cellular immunity against microbial pathogens, specific phytopathogens including bacteria, viruses, and fungi can escape the immunity thereby facilitating plant diseases with concomitant loss in crop yield (Abramovitch et al, 2006; Brown & Allen, 2004; Buttimer et al, 2017; Chen et al, 2020; Cruz et al, 2010; Enebe & Babalola, 2019; González et al, 2007; Hamdoun et al, 2018; Kashyap et al, 2022; Marković et al, 2022; Moral & Trapero, 2012; Nazarov et al, 2020; Nion & Toyota, 2015; Soni et al, 2022; Varun et al, 2017; Zhang et al, 2018; Zhao et al, 2016).…”
Section: Major Plant Pathogens and Plant Diseasesmentioning
confidence: 99%
“…India, a leading papaya-producing country in the world, accounts for a severe infection impact of PaLCuV, including other begomovirus species, which impedes commercial papaya production of papaya plants, and moreover, it could also reduce the growth of the pharmaceutical industry. Therefore, infection of begomovirus associated with PaLCD causes greater loss to the papaya crop, which not only had anatomical and physiological losses, but their pharmacological potential was also significantly diminished ( Soni et al, 2022 ). In India, PaLCD is associated with a complex of 15 begomovirus species, such as Papaya leaf curl virus (PaLCuV), Papaya leaf crumple virus (PaLCrV), Chilli leaf curl virus (ChiLCV), Chilli leaf curl India virus (ChiLCINV), Duranta leaf curl virus (DLCV), Papaya yellow leaf curl virus (PaYLCV), Papaya severe leaf curl virus (PaSLCV), Tomato leaf curl New Delhi virus (ToLCNDV), Tomato leaf curl virus (ToLCV), Cotton leaf curl Multan virus (CLCuMuV), Tomato leaf curl Gujarat virus (ToLCGV), Croton yellow vein mosaic virus (CYVMV), Pedilanthus leaf curl virus (PeLCV), Ageratum enation virus (AEV), and Cotton leaf curl Burewala virus (CLCuBuV).…”
Section: Introductionmentioning
confidence: 99%